Less may be more: how do coach developers reproduce "learner-centred" policy in practice?. Issue 2 (4th May 2021) - Dempsey, Noel; Cope, Ed; Richardson, David J.; Littlewood, Martin A.; Cronin, Colum J.
ABSTRACT: Past research has explored coach developers' practice and called for learner-centred coach education provision. However, understanding of how "learner-centred" policies are reproduced in practice remains partial. In response, a multiple methods case study explored three introductory coach education courses. The Bernsteinian concept of "framing" was introduced to coach education research for the first time, and used to examine how coach developers implemented "learner-centred" policy. A composite creative non-fiction narrative revealed courses have: (1) A high volume of strongly framed assessment; (2) A wide range of strongly framed content; and (3) Coach developers who attempt to weakly frame pedagogic practice. Findings highlight tensions between being "learner-centred" and covering content and assessment that were prescribed by stakeholders in the coach education system. This study provides a significant contribution by connecting policy to practice, and highlighting the challenges of implementing learner-centred education policy.